The tragedy of political theory: the road not taken - Euben, J. Peter (Princeton University Press, 1990)
Cover Page -- Half-title Page -- Title Page -- Copyright Page -- Dedication Page -- Contents -- Preface -- Part I -- Introduction -- Chapter 1: Conventions and Misgivings -- Chapter 2: The Road Not Taken -- Part II -- Greek Tragedy And Political Theory -- Chapter 3: Justice and the Oresteia -- Chapter 4: Identity and the Oedipus Tyrannos -- Chapter 5: Membership and ""Dismembership"" in the Bacchae -- Part III -- Political Theory And Tragedy -- Chapter 6: The Corcyrean Revolution: Corruption, Dismemberment, and Political Theory in Thucydides' History